1997
DOI: 10.3758/bf03209403
|View full text |Cite
|
Sign up to set email alerts
|

The list-strength effect: Strength-dependent competition or suppression?

Abstract: If several items are associated with a common cue, the cued recall of an item is often supposed to decrease as a function of the increase in strength of its competitors' associations with the cue. Evidence for such a list-strength effect has been found in prior research, but this effect could have been caused both by the strength manipulations and by retrieval-based suppression, because the strengthening and the output order ofthe items were confounded. The experiment reported here employed categorizable item … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
56
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(66 citation statements)
references
References 16 publications
10
56
0
Order By: Relevance
“…Rather, it is consistent with the view that interference and part-list cuing are mediated by different mechanisms (Anderson et al, 2000;D. R. Basden & B. H. Basden, 1995;Bäuml, 1997Bäuml, , 2002Ciranni & Shimamura, 1999). On the basis of this view, the present results together with those from prior research indicate that there is more than just one form of retrieval failure and that amnesic patients may show a deficit with respect to one form of retrieval failure but show no deficit with respect to another.…”
Section: Part-list Cuing Versus Interferencesupporting
confidence: 81%
See 1 more Smart Citation
“…Rather, it is consistent with the view that interference and part-list cuing are mediated by different mechanisms (Anderson et al, 2000;D. R. Basden & B. H. Basden, 1995;Bäuml, 1997Bäuml, , 2002Ciranni & Shimamura, 1999). On the basis of this view, the present results together with those from prior research indicate that there is more than just one form of retrieval failure and that amnesic patients may show a deficit with respect to one form of retrieval failure but show no deficit with respect to another.…”
Section: Part-list Cuing Versus Interferencesupporting
confidence: 81%
“…Thus, it might well be the case that amnesics exhibit a normal increase in competition arising from the encoding of additional material but are more susceptible to incongruencies between learning and test. Such a finding would further underscore the fact that retrieval failure can be caused by different mechanisms (Anderson, E. L. Bjork, & R. A. Bjork, 2000; D. R. Basden & B. H. Basden, 1995;Bäuml, 1997Bäuml, , 2002Ciranni & Shimamura, 1999). If so, amnesics may show intact retrieval processes in some situationsbut may be impaired in others.…”
mentioning
confidence: 99%
“…Results from Experiment 3 showed that increases in the number of different responses to be learned in the total set, per pair, and per position, were associated to decreases in performance, corroborating those found in the literature concerned with task complexity, despite their theoretical and procedural differences (e.g., Bauml, 1997;Brehmer, 1992;Coren & Ward, 1989;Ebbinghaus, 1885Ebbinghaus, /1964Kerstholt, 1992;Payne, 1982;Postman, 1972;Ratcliff, Clark, & Shiffrin, 1990;Simon , 1972Simon , , 1974Sundstrom, 1987). It may be relevant to notice that the measure of performance adopted in the present experiment, that is, the area of the function, which can be interpreted as the total duration of precurrent response necessary to learn each current response, is similar to those used in the first experimental investigations of memory (cf.…”
Section: Task Complexity and Precurrent Behaviorsupporting
confidence: 75%
“…Despite the lack of consensus or agreement concerning the best way of theorizing about task complexity, the effects of one variable has been systematically mentioned in investigations following different theoretical traditions. Increases in the number of responses to be learned (or that are possible) in a given situation have been associated with decreases in performance in several different experimental contexts: (a) The increase in the number of items to be memorized in serial learning tasks increased the time to learn each item (ct. Ebbinghaus, 1885Ebbinghaus, /1964; for opposite results, see Deese, 1958); (b) according to information theory, the number of response alternatives, or possible stimuli in the situation, determines the complexity of different tasks (e.g., Coren & Ward, 1989;Simon , 1972Simon , , 1974; (c) decision making research has suggested that the number of choice alternatives is one of the variables that influences task complexity (e.g., Brehmer, 1992;Kerstholt, 1992;Payne, 1982;Sundstrom, 1987); (d) the cued recall of an item decreases as the number of items associated with the same cue increases (e.g., Bauml, 1997;Ratcliff, Clark, & Shiffrin, 1990); and (e) the increase in the number of responses associated with a given stimulus in paired-associates tasks reduced performance in transfer tasks, when compared to the increase in the number of stimuli associated to the same responses (e.g., Postman, 1972).…”
Section: Methodsmentioning
confidence: 99%
“…As we have discussed in the Introduction, Jakab and Raaijmakers might have obtained equivalent retrieval-induced forgetting regardless of competitor strength because they used category cued recall as their final test, which did not allow one to control output order. When participants are free to output items within a category in any order, they are likely to recall the stronger Rp+ items before the weaker Rp-items, and output interference from the Rp+ items can then impair retrieval of the Rp-items (Bäuml, 1997). Thus, whether competition dependent retrieval-induced forgetting occurs may depend on the nature of the final recall test.…”
Section: Retrieval Practice Resultsmentioning
confidence: 99%